1978
DOI: 10.1104/pp.62.4.516
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Delta-Aminolevulinic Acid Dehydrase from Skeletonema costatum, a Marine Plankton Diatom

Abstract: The accumulation of 8-aminolevulinic acid and activities of 8-aminolevulinic acid dehydrase were examined in the marine diatom, Skektonema costatum, grown in the presence of levulinic acid. Levuinic acid concentrations greater than 10 mm affect growth and morphology, and inhibit chlorophyll synthesis. The algae recover from the effects of levulinic acid after 48 hours of exposure. The recovery is characterized by increased cellular cholorphyll content, decreased 8-aminolevulinic acid accumulation, decreased 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Previous studies from our laboratory (19,21) and that of Grumbach et al (9) (4), however, it has been suggested that chang,es in the characteristics of PSU are associated with changes in piiotosynthetic response (3,5,11,20).…”
mentioning
confidence: 83%
“…Previous studies from our laboratory (19,21) and that of Grumbach et al (9) (4), however, it has been suggested that chang,es in the characteristics of PSU are associated with changes in piiotosynthetic response (3,5,11,20).…”
mentioning
confidence: 83%
“…S. costatum (Grev.) Cleve, Woods Hole clone SKEL, was grown on a 14:10 light-dark cycle at 15 C as previously described (10). The cultures were continuously mixed by stirring, and gently bubbled with sterile air by negative pressure.…”
mentioning
confidence: 99%
“…Konis et al (15) have shown that LA prevents the synthesis of CPII, a pigment-protein complex associated with PSII activity, in greening maize leaves. LA is also reported to inhibit respiration in Scenedesmus (21), to stimulate paramylum breakdown in Euglena (23), and to retard cell division in Skeletonema (22). In a preliminary study, Duggan et al (5) afflicted with hereditary tyrosinemia (16).…”
mentioning
confidence: 99%